A new species of the Genus Margattea (Blattodea: Pseudophyllodromiidae) from Yonaguni-jima Island, the Ryukyus, Japan - Hayashi, Koki (Zootaxa, 2024)
A new species of the cockroach genus Margattea Shellford, 1911 (Blattodea: Pseudophyllodromiidae) is described from Yonaguni-jima Island, the Ryukyus, Japan. The new species M. ventrinigra sp. nov. was compared with three species of the same genus on the basis of morphology and mitochondrial DNA sequences (COI and COII): M. satsumana, M. ogatai and M. nimbata.